(untitled) (REMUNOM, 2025)
Physics is considered a very difficult subject to understand, especially in higher education, where it is more technically rigorous. Educational activities with playful characteristics are generally efficient in transforming difficult and boring subjects into enjoyable learning moments. The objective of this study was to develop a didactic game to be implemented in classes of the subject Bases of Physics and Chemistry Applied to Pharmacy (BQF), part of the undergraduate course in Pharmacy. The results of testing the game in a classroom of a class of the subject showed that the game developed was accepted by the class and that the students learned physics concepts while having fun.